Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Effects of light quality on growth and development of protocorm-like bodies of Dendrobium officinale in vitro - Yuan Lin; Jia Li; Bo Li; Tao He; Ze Chun (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

A checklist of the cultivated plants of Yunnan (PR China) - Chun-Yan Li; Guang-Yong Zhang; Karl Hammer; Chun-Yan Yang; Chun-Lin Long (Genetic Resources and Crop Evolution, 2011)